Pemahaman Gembala tentang Bulan Misi dan Kaitannya dengan Gerakan Misi Gereja - Kaborang, Ndawa (Jurnal Teologi Kontekstual Indonesia, 2025)
This study addressed the social and scientific importance of understanding pastors’ perceptions of “Mission Month” and its relationship to church mission movements, particularly within the GKII Central Java 1. The research aimed to analyse how pastors comprehend the significance of Mission Month and how this understanding influences the effectiveness of mission initiatives at the local church level. Using a qualitative phenomenological approach, data were collected through purposive sampling of eight ordained pastors with at least three years of service, employing unstructured and in-depth interviews as well as participatory observation. Results indicated that pastors perceived Mission Month as a strategic period to mobilise congregational participation in evangelism and mission, reinforcing commitment to the church’s vision. The effectiveness of Mission Month was closely linked to the pastors’ transformative leadership and managerial abilities.